Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan (Studi Empiris Perusahaan Manufaktur di BEI periode 2013-2016) - Padmantyo, Sri; Aryati, Nita Dwi (Prosiding University Research Colloquium, 2018)
Dysmenorrhea refers to painful menstruation which appears in theluteal phase that could affect productivity and quality of life, whiledysmenorrhea in adolescents can reduce the concentration of learning.Muscle relaxation therapy is a non-pharmacological treatment that iseffective, efficient and simple therapy as an treatment ofdysmenorrhea. This study was to determine whether the musclerelaxation therapy reduces for dysmenorrhea in adolescents. Thisstudy was conducted in May until September 2017 at Karya HusadaScience Health College . This design was true experimental withrandomized pretest posttest design. Dysmenorrhea screening usingACOG diagnostic criteria, in 207 female students to determine theprevalence of dysmenorrhea and it?s symptoms was recorded in thediary records symptom. Students with dysmenorrhea were divided intoa control group (n=30) and an experimental group (n=30). Students incontrol group received deep breathing relaxation therapy and those inexperimental group received muscle relaxation therapy. The intensityof pain, blood pressure, respiration and pulse were measured 15minutes before being given treatment and would be measured again at15 minutes after giving the treatment during menstrual pain.Instruments used Numerical Rating Scale. Result: Pain intensity beforeand after intervention in intervention and control group were 5,53 ±1,167 vs 4,17 ± 1,053, P = 0,000 and 4,47 ± 1,358 vs 3,87 ± 1,96, P =0,000 . Test paired t-test and Wilcoxon test to see changes in systolic,diastolic and respiratory pressure changes of pulse before and afterrelaxation. Comparison of the effects of muscle relaxation and deepbreathing relaxation with P <0.05 (0.002) with Mann Whitney test.Muscle relaxation therapy was effective in reducing the intensity ofmenstrual pain or dysmenorrhea in adolescents.